2008
DOI: 10.1002/eji.200737824
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T cell help improves CD8+ T cell memory by retained CD27 expression

Abstract: CD4 + T cell help during the priming of CD8 + T lymphocytes imprints the capacity for optimal secondary expansion upon re-encounter with antigen. Helped memory CD8 + T cells rapidly expand in response to a secondary antigen exposure, even in the absence of T cell help and, are most efficient in protection against a re-infection. In contrast, helpless memory CTL can mediate effector function, but secondary expansion is reduced. How CD4 + T cells instruct CD8 + memory T cells during priming to undergo efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 49 publications
(66 reference statements)
3
34
1
Order By: Relevance
“…Other researchers have also found a link between CD27 and IL-2 in memory CD8 + T cell programming. They have demonstrated that CD4 + T cell help is required for maintenance of CD27 expression on memory CD8 + T cells, which facilitated IL-2 expression upon secondary expansion (44).…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have also found a link between CD27 and IL-2 in memory CD8 + T cell programming. They have demonstrated that CD4 + T cell help is required for maintenance of CD27 expression on memory CD8 + T cells, which facilitated IL-2 expression upon secondary expansion (44).…”
Section: Discussionmentioning
confidence: 99%
“…Memory CD8 T cells, generated in the presence of CD4 help, have been reported to express high levels of CD27, and the ligation of CD27 during restimulation has been shown to increase secondary expansion and autocrine IL-2 production. 39 Whatever the reason for these differences, the absolute requirement for CD4 help and the involvement of CD40 and CD40L in producing an optimal H60-specific CD8 response is preserved between the primary and memory responses. It is well known that CD4 help during the primary response gives CD8 T cells a high capacity for expansion upon rechallenge.…”
Section: Discussionmentioning
confidence: 99%
“…Certain studies have suggested that cellular immunity to an influenza vaccine is a useful predictor of protection against disease in the elderly (20). The cellular immune response to an influenza vaccine has been described as the expansion of CD8 + and CD4 + T lymphocytes with surface markers that classify them as effector or memory T cells based on the surface markers CD62L and CD45RA (21)(22)(23)(24); other molecules, including CD27, are costimulatory and indicate activation (25). These surface markers have yet to be characterized in children with cancer who are receiving chemotherapy and who have been immunized with an influenza vaccine.…”
Section: Introductionmentioning
confidence: 99%